Hydrophobic, solid acid catalysts for production of biofuels and lubricants - Sreeprasanth, Pulinthanathu Sree; Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Applied Catalysis A-General, 2006)
A novel application of Fe-Zn double-metal cyanide (DMC) complexes as solid catalysts in the preparation of fatty acid alkyl esters (biodiesel/biolubricants) from vegetable oils is reported. The catalysts are hydrophobic (no H2O adsorption at reaction temperatures) and contain only Lewis acidic sites (NH3 and pyridine adsorption). Bronsted acid sites are absent (absence of 1546 and 1639 cm(-1) bands on adsorption of pyridine). Basic sites are also absent (no CO2 adsorption). Unlike the homogeneous or other solid catalysts (like ZnO-Al2O3, for example), the Fe-Zn, DMC catalysts are highly active even for the simultaneous transesterification of triglycerides and esterification of the free fatty acids (FFA) present in unrefined and waste cooking oils as well as non-edible oils. They are also tolerant of water, probably, due to their surface hydrophobicity. A relationship between the transesterification activity and the concentration of strong Lewis acid sites has been observed. Coordinatively unsaturated Zn2+ ions in the structure of the Fe-Zn complex are the probable active sites. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: alcoholysis of vegetable oils; Biodiesel; Biolubricants; double-metal cyanides (DMC); esterification of free fatty acids; fatty acid alkyl esters; fatty acid methyl esters; solid Fe-Zn catalysts; transesterification of vegetable oils

Lanthanum and zinc incorporated hydrotalcites as solid base catalysts for biodiesel and biolubricants production - Rahul, R.; Satyarthi, Jitendra K.; Srinivas, D. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2011)
Mg-Al hydrotalcites doped with varying amounts of lanthanum and zinc ions (10 30 mol %) have been prepared by co-precipitation method and used, after calcination at 873 K, as solid base catalysts for transesterification of soybean oil with methanol (producing biodiesel) and n-octanol (producing biolubricants). The catalyst with 20 mol % of lanthanum shows the highest transesterification activity (soybean oil conversion = 100 % and biodiesel yield = 95 %) at 423 K in 4 h. Catalytic activity varies in proportion with the basicity of the catalysts.
Keywords: Biodiesel; Biolubricants; catalysis; Doped hydrotalcites; Hydrotalcites; Lanthanum; Solid base catalysts; transesterification; Vegetable oils; zinc

Zirconium phenyl phosphonate phosphite as a highly active, reusable, solid acid catalyst for producing fatty acid polyol esters - Varhadi, Poonam; Kotwal, Mehejabeen; Srinivas, D. (Applied Catalysis A-General, 2013)
The application of zirconium phenyl phosphonate phosphite (ZrPP) as a solid acid catalyst for producing polyol esters by esterification of glycerol or trimethylolpropane with a fatty acid (C-8-C-18.1) is reported for the first time. ZrPP exhibits high catalytic activity and in particular, (di + tri) esters selectivity (92.3 mol%). These esters of polyols are known for their application as biolubricants. The catalyst prepared using phosphorous acid to phenyl phosphonic acid molar ratio of 3:1 was found superior. The influence of process parameters on activity and selectivity of the catalyst was investigated. ZrPP was reusable in at least three recycling experiments. Hydrophobicity due to exposed phenyl groups on the surface is the possible cause for superior esterification activity of this novel, solid catalyst. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Biolubricants; Esterification of fatty acid; Fatty acid glycerides; Hydrophobic solid acid catalyst; Polyol esters; Zirconium phenyl phosphonate phosphite